PINSA Learning Media (Cow Digestion Billboard) on Healthy Food Theme - Yulius Try Widiharto; Khusnul Fajriyah; Kiswoyo Kiswoyo (Universitas Pendidikan Ganesha, 2021)
Interactive learning media has not yet been developed by utilizing visual media to experience abstract learning difficulties. Students do not understand the material during the learning process. This study aims to develop a media billboard for cow digestion that can be used as an alternative media to help the learning process. This type of research is research and development (R&D), with the development model used being the ADDIE model. Respondents in this study were six teachers and 58 fifth-grade elementary school students. This study involved three material experts and three learning media experts. The techniques used in collecting data are interviews, observations, questionnaires, and documentation. The instrument used is a questionnaire. The data analysis technique used is quantitative and qualitative. The results of this study were obtained based on the validity test results from the assessment of the media expert validator with a score of 99% (excellent), learning material expert 98% (excellent). The results of the practicality test were obtained based on the teacher's response assessment of 94% (excellent) and 99% of students (excellent). It can be concluded that the beef digestive billboard media is valid and practical to use on the theme of healthy food, the sub-theme of how the body processes food for fifth-grade elementary school students.